Volume 5A: Heat Transfer 2016
DOI: 10.1115/gt2016-56128
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Studies of Midpassage Gap Leakage and Misalignment for a Non-Axisymmetric Contoured Turbine Blade Endwall

Abstract: Turbine vanes and blades are generally manufactured as single or double airfoil sections that must each be installed onto a turbine disk. Between each section, a gap at the endwalls through the blade passage is present, through which high pressure coolant is leaked. Furthermore, sections can become misaligned due to thermal expansion or centrifugal forces. Flow and heat transfer around the gap is complicated due to the interaction of the mainstream and the leakage flow. An experimental and computational study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The lack of near-wall data motivated computational work. Lange, Lynch, and Lewis (2016) compared their Reynolds averaged Navier-Stokes (RANS) with Cardwell et al's (2005) and their own experiments and noted a number of RANS's inadequacies. In another RANS study, Kim, Chung, Rhee, and Cho (2016) reported the cooling effectiveness as a function of the misalignment's size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of near-wall data motivated computational work. Lange, Lynch, and Lewis (2016) compared their Reynolds averaged Navier-Stokes (RANS) with Cardwell et al's (2005) and their own experiments and noted a number of RANS's inadequacies. In another RANS study, Kim, Chung, Rhee, and Cho (2016) reported the cooling effectiveness as a function of the misalignment's size.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we are able to do DNS because the Reynolds number of the flow is not very high. In Cardwell et al (2005) and Lange et al (2016), the authors matched to engine conditions and the flow's Reynolds number is Re in = U 0 C/๐œˆ = O(10 5 ), where U 0 is the free-stream velocity, C is the chord length and ๐œˆ is the kinematic viscosity. The height of the incoming boundary layer is approximately ๐›ฟ = 0.1C, and therefore the above Reynolds number corresponds to a Reynolds number of Re b = U 0 ๐›ฟ/๐œˆ = O(10 4 ) for the incoming boundary layer: this is quite moderate, and DNSs of boundary layers at this Reynolds numbers are reported in Schlatter and ร–rlรผ (2010) and Pirozzoli, Grasso, and Gatski (2004).…”
Section: Introductionmentioning
confidence: 99%